Queer Dramaturgies International Perspectives on Where Performance Leads Queer - Campbell, Alyson; Farrier, Stephen; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2016)
This international collection of essays forms a vibrant picture of the scope and diversity of contemporary queer performance. Ranging across cabaret, performance art, the performativity of film, drag and script-based theatre it unravels the dynamic relationship performance has with queerness as it is presented in local and transnational contexts.
Keywords: Culture -- Study and teaching; Theater; Theater -- History; Performing arts; Arts; Cultural and Media Studies; Performing Arts; Theatre History; Arts; Theatre and Performance Studies; Electronic books